Comportamento de cultivares de feijão (Phaseolus vulgaris L) no sul do Estado do Espírito Santo - Candal Neto , J F; Vieira , Clibas (Revista Ceres, 2025)
Twenty-eight bean (Phaseolus vulgaris L.) yield trials were carried out in southern Espírito Santo State, Brazil. Two data from each trial were taken: seed production and disease resistance.